RANCANG BANGUN APLIKASI REMINDER PENGUMPULAN SOAL UJIAN DI SMK JAKARTA 1 BERBASIS WEB - Harni Kusniyati; Arum Waruju Jono Putro (Sekolah Tinggi Teknik - PLN, 2018)
The exam is a test to given to assess the lessons that have given by a teacher to student in a period of time. Usually almost every six months the school always organizing the exam like the midterm or the final exams for one semester. Before the semesters started usually a teacher the result are wired to make about submitted to the biannual the organizing committee .To help the committee in conveying information to each teachers and remind teachers to collect the exam questions then a reminder is needed. Reminder is a messaging feature that can help to remind something at a certain time. Reminder application becomes one of the alternatives to help the committee and become a faithful remind for the teacher to make it easy to use to access anywhere and anytime. In this research, the writer will make reminder application to collect test questions in SMK Jakarta 1 by using PHP programming language with notification to teacher's email and committee, and design process flow using UML (Unified Modeling Language).